Ketoconazole induces reversible antifungal drug tolerance mediated by trisomy of chromosome R in Candida albicans - Zheng, Lijun; Xu, Yi; Wang, Chen; Guo, Liangsheng (Frontiers in Microbiology, 2024)
The emergence of tolerance to antifungal agents in Candida albicans complicates the treatment of fungal infections. Understanding the mechanisms underlying this tolerance is crucial for developing effective therapeutic strategies.Objective: This study aims to elucidate the genetic and molecular basis of ketoconazole tolerance in C. albicans, focusing on the roles of chromosomal aneuploidy, Hsp90, and calcineurin.The wild-type C. albicans strain SC5314 was exposed to increasing concentrations of ketoconazole (0.015-32 μg/mL) to select for tolerant adaptors.Disk diffusion and spot assays were used to assess tolerance. Whole-genome sequencing identified chromosomal changes in the adaptors. The roles of Hsp90 and calcineurin in maintaining and developing ketoconazole tolerance were investigated using specific inhibitors and knockout strains.Results: Adaptors exhibited tolerance to ketoconazole concentrations up to 16 μg/mL, a significant increase from the parent strain's inhibition at 0.015 μg/mL. All tolerant adaptors showed amplification of chromosome R, with 29 adaptors having trisomy and one having tetrasomy. This aneuploidy was unstable, reverting to euploidy and losing tolerance in drug-free conditions. Both Hsp90 and calcineurin were essential for maintaining and developing KCZ tolerance. Inhibition of these proteins resulted in loss of tolerance. The efflux gene CDR1 was not required for the development of tolerance. Chromosome R trisomy and tetrasomy induce cross-tolerance to other azole antifungal agents, including clotrimazole and miconazole, but not to other antifungal classes, such as echinocandins and pyrimidines, exemplified by caspofungin and 5-flucytosine. Conclusions: Ketoconazole tolerance in C. albicans is mediated by chromosomal aneuploidy, specifically chromosome R amplification, and requires Hsp90 and calcineurin. These findings highlight potential targets for therapeutic intervention to combat antifungal tolerance and improve treatment outcomes.